Swedish election study 1970 - Särlvik, Bo; Statistics Sweden (University of Gothenburg, 1983)
The 1970 election study differs from the others because the entire survey was carried out after election day. Different techniques were used: about 1/3 of the sample were interviewed in their homes, an additional 1/3 through telephone interviews, and the remainder received a short mail questionnaire. Information on occupation, education, trade union affiliation and political party membership in this survey (the third stage of the 1964-1968-1970 panel) was extracted from the 1968 survey, for all respondents except those lost from the 1968 sample and those added in the 1970 supplementary sample. For these respondents information from 1970 was used. Questions specific to the 1970 election study are those on public representation on bank boards, Swedish membership in the Common Market, and aid to developing countries. There are also questions about the respondent´s opinion of the Social Democratic government, and on what the respondent wants the parties to accomplish on national and local level. Unlike most of the election studies, the 1970 study does not include questions on mass media.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

The 1970 election study differs from the others because the entire survey was carried out after election day. Different techniques were used: about 1/3 of the sample were interviewed in their homes, an additional 1/3 through telephone interviews, and the remainder received a short mail questionnaire. Information on occupation, education, trade union affiliation and political party membership in this survey (the third stage of the 1964-1968-1970 panel) was extracted from the 1968 survey, for all respondents except those lost from the 1968 sample and those added in the 1970 supplementary sample. For these respondents information from 1970 was used. Questions specific to the 1970 election study are those on public representation on bank boards, Swedish membership in the Common Market, and aid to developing countries. There are also questions about the respondent´s opinion of the Social Democratic government, and on what the respondent wants the parties to accomplish on national and local level. Unlike most of the election studies, the 1970 study does not include questions on mass media.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1970
VU70
Keywords: developing countries; utvecklingsland; elections; val; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; religion; religion; social mobility; social rörlighet; international relations; internationella relationer; voting; röstning; political interest; politiskt intresse; political behaviour; politiskt beteende; taxation; beskattning; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; trade unions; fackföreningar; political attitudes; politiska åsikter; agriculture; lantbruk; farming; jordbruk; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap